Penggunaan Modul Visual Interaktif untuk Meningkatkan Literasi Numerik Mahasiswa Baru di Jurusan Fisika Unila - Ayu Aprilia; Suprihatin Suprihatin; Posman Manurung (Lembaga Pengembangan Kinerja Dosen, 2025)
Numerical literacy is a fundamental skill that plays a crucial role in the learning process, particularly in the field of science, especially physics. However, the reality is that many freshmen struggle with numerical literacy. This significantly impacts their foundational mathematical skills, which can hinder the academic learning process. This community service activity aims to enhance the numerical literacy of freshmen in the Physics Department at the University of Lampung by utilizing interactive visual modules. The activity was conducted over two sessions in January 2025, involving 28 new students. The students were divided into heterogeneous groups to support collaborative learning. Pre-test and post-test assessments were conducted to measure the effectiveness of the modules. The results showed an average score improvement from 36.25% to 56.6%. Addionally, the satisfaction survey results showed positive responses regarding the module’s appearance, clarity and benefits. Based on this activity, it was concluded that collaborative learning supported by interactive visual media can enhance students numerical literacy skills.